Comparative water quality study between peat coagulant treated and untreated model water bodies - Mohammed Helaluddin, Abul Bashar; Alaama, Mohamed; Mohd Nawi, Mohd Asri (Asian Research Publishing Network (ARPN), 2018)
Locally invented coagulant from Malaysian peat soil was effective for the clarification of lake and river water. Study was performed on stagnant lake water using model water bodies treated with peat coagulant. Better water quality was found in peat coagulant treated lake water compared to the lake water without peat coagulant treatment. The Dissolved Oxygen (DO) level recovered to the original value within two to three weeks in peat coagulant dosed tank. For the control tank the DO level was as low as 0.8 mg/L and the DO level never reached the original value even after sixty days of monitoring. The other water quality parameters like Chemical Oxygen Demand (COD), nutrients (P and N) and suspended solids were lower than those of the control tank.